Polishing slurry and method of manufacturing semiconductor device
By combining nano-absorbing particles with high Mohs hardness and soft particles with low Mohs hardness in the polishing slurry and ensuring that both have the same zeta potential, the low polishing rate and damage problems of fine-pitch structures are solved, achieving high-efficiency polishing and low damage effects.
Patent Information
- Application Number
- CN202411485117.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-21
- Filing Date
- 2024-10-23
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when polishing using fine abrasive particles, the polishing rate is low and it is difficult to effectively polish the fine-pitch structure, and there are problems of structural damage such as surface scratches and shape deformation.
A polishing slurry containing nano-absorbent particles with a hardness of more than 5 Mohs and soft particles with a low Mohs hardness, both of which have the same zeta potential in the slurry, is used to improve the polishing efficiency of the nano-absorbent particles.
The polishing rate is significantly improved and surface damage, such as surface scratches and shape deformation, enables the manufacture of high-performance semiconductor devices with fine pitches of about 10 nm or less.
Smart Images

Figure HDA0005098524920000011 
Figure HDA0005098524920000021 
Figure HDA0005098524920000031
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2023-0142810 filed on October 24, 2023, and Korean Patent Application No. 10-2024-0144114 filed on October 21, 2024, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference. Technical Field
[0003] Example embodiments relate to polishing slurries and methods of manufacturing semiconductor devices using the same. Background Art
[0004] Semiconductor devices require a structure with a flat surface during the manufacturing process. The structure can be formed by a polishing process. The polishing process may include chemical mechanical polishing (CMP). Chemical mechanical polishing includes providing a polishing slurry containing abrasive (abrasive) particles between a substrate to be polished and a polishing pad, while rotating the semiconductor substrate in contact with the polishing pad to flatten the surface of the semiconductor substrate by pressing and rotating it.
[0005] Recently, high performance and highly integrated semiconductor devices require fine pitch structures. Fine abrasive particles with a very small particle size range are being studied to effectively polish fine pitch structures. However, when fine abrasive particles are used, the polishing rate tends to be lower. Therefore, there is a need for a new method that can achieve both effective polishing of fine pitch structures and improvement of polishing rates. Summary of the invention
[0006] Certain example embodiments provide new polishing slurries that can simultaneously improve polishing rate and efficiency while reducing structural damage (margin) such as surface scratches and shape deformation.
[0007] Some example embodiments provide methods of manufacturing a semiconductor device using the polishing slurry.
[0008] Polishing slurries according to some example embodiments include nanoabrasive particles having a Mohs hardness greater than about 5, and soft particles having a Mohs hardness lower than the nanoabrasive particles, wherein the nanoabrasive particles and the soft particles have the same sign of zeta potential as each other in the slurry.
[0009] The soft particles may include polymer particles.
[0010] The difference in Mohs hardness between the soft particles and the nanoabrasive particles may be greater than or equal to about 1.
[0011] The soft particles may have a larger average particle size than the nanoabrasive particles.
[0012] The nanoabrasive particles may have an average particle diameter of less than or equal to about 100 nanometers.
[0013] The average particle diameter of the soft particles may be about 50 nm to about 20 μm.
[0014] The nanoabrasive particles and the soft particles may have the same zeta potential in the slurry.
[0015] The soft particles may include polymer particles, which include polystyrene, styrene-based copolymers, poly(alkyl (meth)acrylates), acrylic (acryloyl) copolymers, polyvinyl chloride, polyacetal, saturated polyester, polyamide, polyimide, poly(amide-imide) copolymer, polycarbonate, phenoxy resin, polyolefin, olefin-based copolymer, polyurea, polyurethane, melamine resin, epoxy resin, or any combination thereof.
[0016] The nanoabrasive particles may include metal oxides, metal nitrides, metal fluorides, metal carbides, or any combination thereof.
[0017] The metal oxide may include silicon oxide, cerium oxide, titanium oxide, zirconium oxide, aluminum oxide, molybdenum oxide, ruthenium oxide, tantalum oxide, tungsten oxide, or any combination thereof; the metal nitride may include silicon nitride, aluminum nitride, titanium nitride, boron nitride (cubic structure), or any combination thereof; the metal fluoride may include calcium fluoride (CaF 2 ), selenium fluoride (SeF 4 ), tellurium fluoride (TeF 4 ), or any combination thereof, and the metal carbide may include tantalum carbide, boron carbide, or any combination thereof.
[0018] The soft particles may be included in the polishing slurry in an amount of about 0.01 weight percent (wt%) to about 15 wt%, and the nanoabrasive particles may be included in the polishing slurry in an amount of about 0.01 wt% to about 15 wt%, based on the total weight of the polishing slurry.
[0019] The soft particles and the nanoabrasive particles may be present in the slurry in a weight ratio of about 0.1:1 to about 5:1.
[0020] The soft particles and the nano-abrasive particles may be present in the slurry in a volume ratio of about 1:1 to about 30:1.
[0021] The soft particles may be spherical.
[0022] In the polishing slurry, both the soft particles and the nanoabrasive particles may have a positive zeta potential, or both the soft particles and the nanoabrasive particles may have a negative zeta potential.
[0023] The polishing slurry may further include a chelating agent, an oxidizing agent, a surfactant, a dispersant, a pH adjuster, or any combination thereof.
[0024] A method of manufacturing a semiconductor device according to some example embodiments includes arranging a surface of a semiconductor substrate and a surface of a polishing pad close to each other, supplying a polishing slurry according to some example embodiments between the semiconductor substrate and the polishing pad, and polishing the surface of the semiconductor substrate by bringing the surface of the semiconductor substrate into contact with the surface of the polishing pad.
[0025] Supplying the polishing slurry according to some example embodiments may include supplying the polishing slurry between the semiconductor substrate and the polishing pad at a rate of about 10 milliliters / minute (ml / min) to about 300 ml / min.
[0026] Polishing of the surface of the semiconductor substrate may be performed at a pressure of about 1 psi to about 10 psi against the surface.
[0027] The polishing slurry may polish the metal wire present at the surface of the semiconductor substrate. Therefore, the semiconductor substrate may include the metal wire at the surface of the semiconductor substrate, and the polishing of the surface of the semiconductor substrate polishes the metal wire.
[0028] The polishing slurry according to some example embodiments can improve the polishing rate and polishing efficiency, and optionally reduce or minimize surface damage such as surface scratches and shape deformation of fine pitch structures. As a result, based on one or more surfaces of a semiconductor device (e.g., a semiconductor wafer) polished using the polishing slurry, a high-performance, highly integrated semiconductor device including a structure with a fine pitch of about 10 nm or less with reduced or minimized defects or no defects can be manufactured. The polishing slurry is easy to manufacture and uses inexpensive materials, and therefore the manufacturing cost is also low. Therefore, the use of the polishing slurry in a polishing process, for example, for polishing a semiconductor wafer, can reduce the manufacturing cost of manufacturing a semiconductor device using a structure having one or more surfaces polished using the polishing slurry. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 is a diagram schematically showing an operating principle of a polishing slurry according to some example embodiments.
[0030] Figures 2 to 8 is a cross-sectional view showing a manufacturing process of shallow trench isolation (STI) according to some example embodiments.
[0031] Fig. 9 is a diagram schematically showing an exemplary chemical mechanical polishing apparatus.
[0032] Fig.10: are graphs showing polishing rates of two slurries including (only) cerium oxide particles having respective different particle sizes according to Reference Example 1, and a slurry including soft polymer particles alone.
[0033] Fig.11 is a graph showing polishing rates of three slurries including two slurries (A and B) respectively including cerium oxide and different types of polystyrene having the same zeta potential sign as cerium oxide according to Example 1, and a slurry alone including cerium oxide having a size of 25 nm (STD: standard).
[0034] Fig.12 is a graph showing the polishing rates of three slurries including two slurries (A and B) respectively including cerium oxide and different types of polystyrene having the same zeta potential sign as cerium oxide according to Example 2, and a slurry alone including cerium oxide having a size of 15 nm (STD: standard).
[0035] Fig.13 is a graph showing the polishing rates of two slurries including one slurry (A) including silicon dioxide and a polymer having the same zeta potential sign as silicon dioxide according to Example 3, and another slurry (Silicon Dioxide) including only silicon dioxide having a size of 7 nm.
[0036] Fig.14 is a graph showing polishing rates of five (5) slurries including polystyrene having the same zeta potential sign as ceria in different amounts according to Example 4, and a slurry including ceria having a size of 25 nm alone (STD: Standard).
[0037] Fig.15 is a graph showing the polishing rates of five (5) slurries including two slurries (positive A and positive B) respectively including ceria and different types of polystyrene having the same zeta potential sign as ceria according to Example 5, two slurries (negative A and negative B) respectively including ceria and different types of polymers having opposite zeta potential signs as ceria, and a slurry alone including ceria having a size of 25 nm.
[0038] Fig.16 yes Fig.15 Photograph of the negative A slurry.
[0039] Fig.17 are photographs of two bottles, one (left) containing a mixture to which a polymer having a zeta potential of the opposite sign to that of the silica particles has been added, and the other (right) containing a mixture to which a polymer having a zeta potential of the same sign as that of the silica particles has been added.
[0040] Fig.18 is a graph showing the polishing rates of a slurry in which a polymer having a zeta potential sign identical to that of silicon dioxide is mixed (negative), a slurry in which a polymer having a zeta potential sign opposite to that of silicon dioxide is mixed (positive), and a slurry including silicon dioxide particles alone (silicon dioxide).
[0041] Fig.19 Photographs showing the surface of a semiconductor wafer polished with a slurry comprising ceria alone having a particle size of 50 nm (left), a slurry comprising ceria alone having a particle size of 25 nm (center), and a slurry comprising ceria having a particle size of 25 nm and polystyrene having a particle size of 83 nm (right), measured using AFM (atomic force microscopy).
[0042] Fig. 20 Photographs measured with AFM show the surface of a semiconductor wafer polished with a slurry comprising silicon dioxide alone having a particle size of 7 nm (left) and a slurry comprising the silicon dioxide together with a polymer having a particle size of 100 nm (right).
[0043] Fig.21 is a schematic block diagram of an electronic device according to some example embodiments. DETAILED DESCRIPTION
[0044] Hereinafter, some example embodiments are described in detail so that those skilled in the art can easily implement them. However, the structure of actual application can be implemented in many different forms and is not limited to the example embodiments described herein.
[0045] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly dictates otherwise, a singular expression includes a plural expression.
[0046] As used herein, "any combination thereof" refers to a mixture, stack, composite, copolymer, alloy, blend, reaction product, and / or the like of the constituent parts (ingredients).
[0047] As used herein, "metal" may include semi-metals as well as metals.
[0048] As used herein, "Mohs hardness" is a relative value compared to a reference material (see https: / / en.wikipedia.org / wiki / Mohs_scale). As described herein, "Mohs hardness" may be a relative value of hardness compared to a reference material, the reference material being talc (Mg 3 Si 4 O 10(OH) 2 ), wherein talc has a Mohs hardness of 1.
[0049] Herein, it should be understood that terms such as “comprising”, “including” or “having” are intended to indicate the presence of the stated features, quantities, steps, elements, or any combination thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or any combination thereof.
[0050] In the accompanying drawings, the thickness of layers, films, panels, regions, etc. is exaggerated for clarity. The same reference numerals represent the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or there may be intermediate elements. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0051] Furthermore, the term "layer" as used herein includes not only a shape formed on the entire surface when viewed from a plan view but also a shape formed on a partial surface.
[0052] As used herein, "size" means the average particle diameter in the case of a sphere and the length of the longest part in the case of a non-spherical shape. The size can be measured by methods well known to those skilled in the art, for example, by a particle size analyzer, or by a transmission electron micrograph or a scanning electron micrograph. Alternatively, the average particle size (diameter) value can be obtained by measuring using a dynamic light scattering method, performing data analysis, counting the number of particles for each particle size range, and calculating from these data. Unless otherwise defined, the average particle diameter may refer to the diameter (D50) of particles having a cumulative volume of 50% by volume in a particle size distribution. In addition, when "size" or "particle size" is mentioned alone, it refers to the "average particle size". The term "average" as used herein refers to the mean average.
[0053] In the present disclosure, the term "or" will not be interpreted as an exclusive meaning, and for example, "A or B" is interpreted to include A, B, A+B, and / or the like.
[0054] Advanced high-performance highly integrated semiconductor devices require fine pitch structures of about 10 nm or less. Conventional abrasive slurries including abrasive particles having a particle size of tens of nanometers can cause damage to the fine pitch structures such as surface scratches and shape deformation. Therefore, in order to effectively polish fine pitch structures, fine abrasive particles having a particle size of several nanometers are of interest and are being studied to replace existing abrasive particles having a particle size of tens of nanometers. However, these fine abrasive particles have a low or inefficient polishing rate, and therefore, improvements in polishing performance are needed and sought.
[0055] The conventional method is to increase the size of abrasive particles to increase the removal rate (RR), but this results in many defects such as scratches on the surface of semiconductor devices. In addition, it is not suitable to use large-sized abrasive particles to polish high-performance, highly integrated semiconductor devices that require fine pitch structures of about 10 nm or less.
[0056] Another approach to increase polishing rates is to synthesize new shaped or functionalized abrasive particles. However, this is cumbersome because it requires multiple synthesis steps and the associated time and labor consumption.
[0057] A method for preparing a semiconductor surface by using ceria and SiO 2 The method of inducing strong chemical bonds between the two can be to control the ionic valence of the surface of ceria, i.e., Ce 3+ / Ce 4+ However, controlling the ionic valence of ceria surface usually requires high-temperature reduction reaction using hydrogen (which has high temperature and explosion risk), or doping with expensive transition metal or noble metal atoms.
[0058] The polishing slurry according to some example embodiments does not suffer from any of the problems of the existing methods and can be easily manufactured with inexpensive materials. In addition, when a polishing process is performed using the prepared polishing slurry according to the embodiments, an excellent polishing effect and a significantly improved polishing rate can be achieved.
[0059] In particular, polishing slurries according to some example embodiments include soft particles having a Mohs hardness of less than or equal to about 5, and nanoabrasive particles, wherein in the slurry, the soft particles and the nanoabrasive particles have a zeta potential of the same sign.
[0060] That is, in addition to the nano-sized abrasive particles, the polishing slurry according to some example embodiments also includes soft particles that do not directly participate in polishing because their Mohs hardness is significantly lower than that of the material to be polished, such as SiO2, which forms the semiconductor material. 2The soft particles and the abrasive particles have a Mohs hardness of 0.040mm and a zeta potential of the same sign in the slurry, so that the particles do not form aggregates in the slurry, the polishing rate of the nano-sized abrasive particles is improved, and the surface defects of the material to be polished are reduced.
[0061] Will refer to Figure 1 The operating principles of polishing slurries according to some example embodiments are described.
[0062] Figure 1 1 is a schematic diagram schematically showing a case where abrasive grains (represented by A, B and C) having a Mohs hardness greater than about 5 and soft grains D having a Mohs hardness lower than the abrasive grains are used to polish a surface of a material to be polished, such as a semiconductor wafer 1.
[0063] like Figure 1 As shown in , when the surface of the semiconductor wafer 1 is polished using abrasive grains A and abrasive grains B, respectively, in proportion to the size of the abrasive grains, when polishing is performed by using abrasive grains A having a larger particle size, the polishing rate is higher than that of abrasive grains B having a smaller particle size. In the case of abrasive grains B having a small particle size, not only is the contact area with the surface of the semiconductor wafer 1 small, but also the load transmitted from the polishing head is not sufficiently transmitted, resulting in a much lower polishing rate than that of abrasive grains A. For example, when the size of the abrasive grains is reduced from about 100 nm to about 22 nm, the polishing rate can be reduced by about 80% or more.
[0064] On the other hand, the larger the abrasive particles, the larger the size of the surface scratches of the material to be polished. That is, the size of the surface scratches is proportional to the size of the abrasive particles. Therefore, in order to reduce the surface scratches, abrasive particles with a smaller particle size must be used. In this case, the problem of reducing the polishing rate as described above should be solved.
[0065] exist Figure 1 , the abrasive particles C are shown polishing the surface of the semiconductor wafer 1 while in contact with the soft particles D. As described above, the soft particles D are made of a material having a Mohs hardness lower than that of the abrasive particles, and are basically a material that cannot polish the surface of the semiconductor wafer 1 alone. Figure 1 As shown in , when the soft particles D come into contact with the abrasive particles C, the load applied from the polishing head can be well transferred to the abrasive particles C through the soft particles D. In this case, even if the abrasive particles C have a small particle size, the load can be better transferred to the abrasive particles C through the soft particles D than in the case where the abrasive particles are used alone. That is, compared with using the abrasive particles B having the same particle size as the abrasive particles C alone, a much higher polishing rate can be obtained. Here, as Figure 1As schematically shown in , the soft particles D can be made to have a much larger particle size than the abrasive particles C, so that a higher load can be transferred to the abrasive particles C, thereby achieving a higher polishing rate. At the same time, because the soft particles D themselves may not polish the surface of the semiconductor wafer 1, even if there are soft particles D with a much larger particle size in the polishing slurry, there is almost no worry about increasing scratches on the surface of the polishing object (object). In summary, the polishing slurry according to some example embodiments includes soft particles that do not have polishing ability due to low Mohs hardness together with nano-sized abrasive particles to achieve the surprising effect of improving the polishing rate and reducing surface scratches. As a result, based on one or more surfaces of a semiconductor device polished using a polishing slurry according to an embodiment, a high-performance, highly integrated semiconductor device including a structure with a fine pitch of about 10nm or less with reduced or minimized defects or no defects can be manufactured.
[0066] In addition, the soft particles and abrasive particles in the polishing slurry according to some example embodiments have zeta potentials with the same sign. As can be seen from the examples and comparative examples to be described below, when the abrasive particles and the soft particles have zeta potentials with opposite signs to each other, the two types of particles may be adsorbed to each other in the slurry due to electrostatic attraction between the particles, which may increase the particle size in the slurry and thus cause precipitation. In other words, particles with zeta potentials with different signs may mix and adsorb in the slurry to form a precipitate, and thus make the slurry non-uniform, resulting in a reduction in the polishing efficiency of the slurry and / or defects in the polishing product (product).
[0067] In the polishing slurry according to some example embodiments, the soft particles and the abrasive particles may have a zeta potential having the same sign, and there is neither adsorption nor agglomeration between the particles due to electrostatic repulsion, or there is no precipitation generated therefrom. Therefore, the polishing slurry according to some example embodiments may maintain a uniform state and exhibit the effects of high polishing rate and low (few) surface scratch generation as described above. As a result, the performance of the polishing slurry 410 may be improved in the following aspects: facilitating the polishing of a surface, having reduced, minimized, or prevented damage to the surface being polished, and based on one or more surfaces of a semiconductor device polished using the polishing slurry 410, a high-performance, highly integrated semiconductor device including a structure having a fine pitch of about 10 nm or less with reduced or minimized defects or no defects may be manufactured.
[0068] The zeta potential of soft particles and abrasive particles can be changed according to the pH of the polishing slurry. Therefore, the pH of the polishing slurry according to some example embodiments can be adjusted and maintained within the range where the soft particles and abrasive particles can have a zeta potential with the same sign in the polishing slurry. In some embodiments, within a specific pH range, if a specific abrasive particle has a positive or negative zeta potential, a soft particle material with the same positive or negative zeta potential sign can be selected and combined with it. Alternatively, the chemical structure of the material forming the soft particles and / or abrasive particles can be changed, or the surface of the particles can be modified by a specific functional group so that each of the two particles can have a positive or negative zeta potential within a specific pH range. Various methods for changing the zeta potential of a specific material are well known to those skilled in the art. Those skilled in the art can select an appropriate method to adjust the soft particles and abrasive particles in the polishing slurry according to some example embodiments to have a zeta potential with the same sign.
[0069] In some example embodiments, the pH of the polishing slurry may be adjusted to a range of about 2 to about 9, for example, a pH range of about 3 to about 8, a pH range of about 3 to about 7, or a range of about 4 to about 6, and both the soft particles and the abrasive particles included in the polishing slurry may be selected from soft particles and abrasive particles having a positive zeta potential. In some example embodiments, the pH of the polishing slurry may be adjusted to the above ranges, and the soft particles and the abrasive particles included in the slurry may be selected from soft particles and abrasive particles both having a zeta potential having a negative sign (e.g., a negative zeta potential).
[0070] In some example embodiments, the soft particles and abrasive particles included in the polishing slurry may have the same zeta potential as each other. In this case, agglomeration between the soft particles and the abrasive particles may be more effectively reduced, minimized, or prevented, thereby enhancing or maximizing the synergistic effect of the mixture including soft particles and abrasive particles having different sizes and different hardnesses. As a result, the performance of the polishing slurry 410 may be improved in terms of facilitating the polishing of a surface with reduced, minimized, or prevented damage to the surface being polished.
[0071] As long as the soft particles have a zeta potential of the same sign as the nanoabrasive particles within a certain pH range in the polishing slurry, for example, the same zeta potential as the nanoabrasive particles, have a Mohs hardness lower than that of the nanoabrasive particles, for example, a Mohs hardness lower than that of the material to be polished, have substantially no polishing ability itself, and have a larger particle size than that of the nanoabrasive particles, any material can be selected and used as the soft particles without limitation.
[0072] For example, the soft particles can have a Mohs hardness lower than that of the abrasive particles, for example, about 4.9 or less, about 4.8 or less, about 4.7 or less, about 4.6 or less, about 4.5 or less, about 4.4 or less, about 4.3 or less, about 4.2 or less, about 4.1 or less, about 4.0 or less, about 3.9 or less, about 3.8 or less, about 3.7 or less, about 3.6 or less, about 3.5 or less, about 3.4 or less, about 3.3 or less, about 3.2 or less, about 3.1 or less, about 3.0 or less, or about 2.5 or less, and the soft particles can have a Mohs hardness greater than or equal to about 0.1, greater than or equal to about 0.2, greater than or equal to about 0.3, greater than or equal to about 0.4, or greater than or equal to about 0.5.
[0073] When having a Mohs hardness within the above range, the soft particles may not participate in the actual polishing process in a typical chemical mechanical polishing process. This is because the Mohs hardness within the above range may be a Mohs hardness level lower than the Mohs hardness of the polishing object to be polished. In some example embodiments, the soft particles should not participate in a substantial polishing process in a typical chemical mechanical polishing process.
[0074] The nanoabrasive particles may be any nanoabrasive particles used in a chemical mechanical polishing process, and for example, those having a Mohs hardness greater than about 5 may be used. For example, the Mohs hardness of the nanoabrasive particles may be greater than or equal to about 5.5, greater than or equal to about 5.6, greater than or equal to about 5.7, greater than or equal to about 5.8, greater than or equal to about 5.9, greater than or equal to about 6.0, greater than or equal to about 6.1, greater than or equal to about 6.2, greater than or equal to about 6.3, greater than or equal to about 6.4, greater than or equal to about 6.5, or greater than or equal to about 7.0, and the Mohs hardness of the nanoabrasive particles may be less than or equal to about 10, for example, less than or equal to about 9. The nanoabrasive particles have a Mohs hardness within the above range, and thus may participate in an actual polishing process within the polishing slurry according to some example embodiments.
[0075] In the polishing slurry according to some example embodiments, the soft particles and the nano abrasive particles each have a Mohs hardness within the above range, so that the polishing slurry according to some example embodiments including them together can achieve a high polishing rate while minimizing damage (e.g., surface scratches) and shape deformation of the structure to be polished.
[0076] The difference in Mohs hardness between the soft particles and the nano-abrasive particles may be greater than or equal to about 1, for example, greater than or equal to about 1.5, greater than or equal to about 2, greater than or equal to about 2.5, greater than or equal to about 3, greater than or equal to about 3.5, greater than or equal to about 4, greater than or equal to about 4.5, greater than or equal to about 5.0, greater than or equal to about 5.5, or greater than or equal to about 6.0. In addition, the difference in Mohs hardness between the soft particles and the abrasive particles may be less than about 10, less than or equal to about 9.0, less than or equal to about 8.0, or less than or equal to about 7.0. When the difference in Mohs hardness between the soft particles and the nano-abrasive particles is within the above range, a high-performance, highly integrated semiconductor device can be manufactured based on one or more surfaces: surface defects of semiconductor devices having a fine pitch structure of about 10nm or less are reduced, minimized, or eliminated.
[0077] In the polishing slurry according to some example embodiments, the nanoabrasive particles may have an average particle diameter of about 1 nanometer (nm) to about 1000 nm, such as less than or equal to about 100 nm, such as less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 45 nm, less than or equal to about 40 nm, less than or equal to about 35 nm, less than or equal to about 30 nm, less than or equal to about 25 nm, less than or equal to about 20 nm, less than or equal to about 15 nm, less than or equal to about 10 nm, or less than or equal to about 5 nm, and In addition, the average particle diameter of the nano abrasive particles can be greater than or equal to about 1nm, for example, greater than or equal to about 2nm, greater than or equal to about 3nm, greater than or equal to about 4nm, greater than or equal to about 5nm, greater than or equal to about 10nm, greater than or equal to about 15nm, greater than or equal to about 20nm, greater than or equal to about 25nm, greater than or equal to about 30nm, greater than or equal to about 35nm, greater than or equal to about 40nm, greater than or equal to about 45nm, greater than or equal to about 50nm, greater than or equal to about 60nm, greater than or equal to about 70nm, greater than or equal to about 80nm, or greater than or equal to about 90nm, but not limited to these scopes. If the size of the nano abrasive particles is in the above scope, during the polishing process using the polishing slurry comprising the nano abrasive particles, the surface defect problem of the polishing object such as surface scratches may not occur.
[0078] The nanoabrasive particles may have a spherical shape, but are not limited thereto. As defined above, the average particle diameter of spherical particles refers to the diameter of particles having 50% by volume of the cumulative volume in the particle size distribution (D 50 ).
[0079] In the polishing slurry according to some example embodiments, when the size of the nanoabrasive particles is selected within the above range, the soft particles may be selected to have an average particle size larger than the particle size of the selected nanoabrasive particles, and the range of the average particle size is not particularly limited. When the size of the soft particles is larger than the size of the nanoabrasive particles, as described above, even if the individual soft particles do not have polishing ability, the large-sized soft particles can effectively transfer the load applied from the polishing head to the nanoabrasive particles, improving the polishing efficiency and polishing rate. For example, the average particle size of the soft particles may be between about 50nm and about 20μm, for example, greater than or equal to about 60nm, greater than or equal to about 70nm, greater than or equal to about 80nm, greater than or equal to about 90nm, greater than or equal to about 100nm, greater than or equal to about 200nm, greater than or equal to about 300nm, greater than or equal to about 400nm, greater than or equal to about 500nm, greater than or equal to about 1μm, greater than or equal to about 1.5μm, greater than or equal to about 2μm , greater than or equal to about 2.5 μm, greater than or equal to about 3 μm, greater than or equal to about 3.5 μm, greater than or equal to about 4 μm, greater than or equal to about 4.5 μm, greater than or equal to about 5 μm, greater than or equal to about 5.5 μm, greater than or equal to about 6 μm, greater than or equal to about 7 μm, greater than or equal to about 8 μm, greater than or equal to about 9 μm, greater than or equal to about 10 μm, greater than or equal to about 11 μm, greater than or equal to about 12 μm, greater than or equal to about 13 μm, greater than or equal to about 14 μm, about 15 μm or more, about 16 μm or more, about 17 μm or more, about 18 μm or more, or about 19 μm or more and about 20 μm or less, for example, about 19 μm or less, about 18 μm or less, about 17 μm or less, about 16 μm or less, about 15 μm or less, about 14 μm or less, about 13 μm or less, about 12 μm or less. m, less than or equal to about 11 μm, less than or equal to about 10 μm, less than or equal to about 9 μm, less than or equal to about 8 μm, less than or equal to about 7 μm, less than or equal to about 6 μm, less than or equal to about 5 μm, less than or equal to about 4 μm, less than or equal to about 3 μm, less than or equal to about 2 μm, less than or equal to about 1 μm, less than or equal to about 0.5 μm, less than or equal to about 0.3 μm, or less than or equal to about 0.1 μm, but are not limited to these ranges.
[0080] The soft particles may have a spherical shape, but are not limited thereto, and may have a shape close to a spherical shape, such as an irregular polyhedron shape, wherein the soft particles in some example embodiments may not be plate-shaped particles.
[0081] The soft particles may include organic materials or inorganic materials.
[0082] If the soft particles include an inorganic material, the inorganic material may include a spherical inorganic material having a low Mohs hardness, for example, a Mohs hardness of about 5 or less (e.g., about 0.1 to about 5, about 0.2 to about 5, about 0.3 to about 5, about 0.4 to about 5, or about 0.5 to about 5). The spherical inorganic material having a low Mohs hardness may include, for example, a spherical inorganic material having pores and thus having a low apparent hardness, but is not limited thereto.
[0083] If soft particles include organic materials, the organic materials may include polymers. In this article, because Mohs hardness is a scale that indicates the hardness of a mineral, it is necessary to convert the hardness of a polymer into Mohs hardness. According to known literature, the Mohs hardness of a polymer may be in the range of about 1.5 to about 2.5. Because the nano abrasive particles included in the polishing slurry according to some example embodiments have a Mohs hardness greater than about 5 (e.g., about 5 to about 10, about 5 to about 9, about 5 to about 8, or about 5 to about 7), most polymers may be used as soft particles in the slurry according to some example embodiments.
[0084] For example, the soft particles may be polymer particles, such as polystyrene, styrene-based copolymers, poly(alkyl (meth)acrylates), acrylic copolymers, polyvinyl chloride, polyacetal, saturated polyester, polyamide, polyimide, poly(amide-imide) copolymer, polycarbonate, phenoxy resin, polyolefin, olefin-based copolymer, polyurea, polyurethane, melamine resin, epoxy resin, or any combination thereof, and are not limited thereto.
[0085] The soft particles may be selected from commercially available materials or materials synthesized by known methods. Since the soft particles in the polishing slurry according to some example embodiments should have a zeta potential having a specific sign, a material having a zeta potential having such a sign may be selected, or the selected material may be modified by known methods to have such a zeta potential in the polishing slurry according to some example embodiments.
[0086] In some example embodiments, the soft particles may include a polymer (homopolymer) or copolymer based on polystyrene. When the soft particles include a polymer or copolymer based on polystyrene, its functional group may be modified to have a positive zeta potential or a negative zeta potential within a specific pH range. For example, as a polymer or copolymer based on polystyrene, polystyrene, poly(styrene-(vinylbenzyl)trimethylammonium chloride) and the like may be used as materials with a positive zeta potential, and as materials with a negative zeta potential, sodium polystyrene sulfonate (polystyrene-NaSS), poly(styrene-divinylbenzene sulfonate sodium) (poly(styrene-divinylbenzene-NaSS)) and the like may be used, but are not limited thereto.
[0087] The nanoabrasive particles may be selected from any abrasive particles useful in a chemical mechanical polishing process and are not limited to a specific type of abrasive particles.
[0088] The nanoabrasive particles may include metal oxides, metal nitrides, metal fluorides, metal carbides, or any combination thereof. For example, metal oxides may include silicon oxide, cerium oxide, titanium oxide, zirconium oxide, aluminum oxide, molybdenum oxide, ruthenium oxide, tantalum oxide, tungsten oxide, or any combination thereof; metal nitrides may include silicon nitride, aluminum nitride, titanium nitride, boron nitride (cubic structure), or any combination thereof; metal fluorides may include calcium fluoride (CaF 2 ), selenium fluoride (SeF 4 ), tellurium fluoride (TeF 4 ), or any combination thereof, and the metal carbide may include tantalum carbide, boron carbide, or any combination thereof.
[0089] The nanoabrasive particles may be included in an amount of about 0.01 wt % to about 15 wt % based on the total weight of the polishing slurry according to some example embodiments. For example, the nanoabrasive particles can be included in an amount greater than or equal to about 0.01 wt %, greater than or equal to about 0.02 wt %, greater than or equal to about 0.03 wt %, greater than or equal to about 0.04 wt %, greater than or equal to about 0.05 wt %, greater than or equal to about 0.06 wt %, greater than or equal to about 0.07 wt %, greater than or equal to about 0.08 wt %, greater than or equal to about 0.09 wt %, greater than or equal to about 0.1 wt %, greater than or equal to about 0.15 wt %, greater than or equal to about 0.2 wt %, greater than or equal to about 0.4 wt %, greater than or equal to about 0.5 wt %, greater than or equal to about 1 wt %, greater than or equal to about 2 wt %, greater than or equal to about 3 wt %, greater than or equal to about 5 wt %, greater than or equal to about 10 wt %, greater than or equal to about 11 wt %, greater than or equal to about 12 wt %, greater than or equal to about 13 wt %, or greater than or equal to about 14 wt %. For example, the nanoabrasive particles may be included in an amount of about 14 wt % or less, about 13 wt % or less, about 12 wt % or less, about 11 wt % or less, about 10 wt % or less, about 9 wt % or less, about 8 wt % or less, about 7 wt % or less, about 6 wt % or less, about 5 wt % or less, about 4 wt % or less, about 3 wt % or less, about 2 wt % or less, or about 1 wt % or less, based on the total weight of the polishing slurry according to some example embodiments, but are not limited thereto.
[0090] By including the nanoabrasive particles within the above range, the polishing slurry according to some example embodiments may effectively polish a fine pitch structure while minimizing surface damage to a polishing object, and may also improve a polishing rate and a polishing efficiency.
[0091] The soft particles may be included in an amount of about 0.01 wt % to about 15 wt % based on the total weight of the polishing slurry according to some example embodiments. For example, the soft particles may be included in an amount greater than or equal to about 0.01 wt %, greater than or equal to about 0.02 wt %, greater than or equal to about 0.03 wt %, greater than or equal to about 0.04 wt %, greater than or equal to about 0.05 wt %, greater than or equal to about 0.06 wt %, greater than or equal to about 0.07 wt %, greater than or equal to about 0.08 wt %, greater than or equal to about 0.09 wt %, greater than or equal to about 0.1 wt %, greater than or equal to about 0.15 wt %, greater than or equal to about 0.2 wt %, greater than or equal to about 0.4 wt %, greater than or equal to about 0.5 wt %, greater than or equal to about 1 wt %, greater than or equal to about 2 wt %, greater than or equal to about 3 wt %, greater than or equal to about 5 wt %, greater than or equal to about 10 wt %, greater than or equal to about 11 wt %, greater than or equal to about 12 wt %, greater than or equal to about 13 wt %, or greater than or equal to about 14 wt %. In addition, based on the total weight of the polishing slurry according to some example embodiments, soft particles may be included in an amount of less than or equal to about 14 wt.%, less than or equal to about 13 wt.%, less than or equal to about 12 wt.%, less than or equal to about 11 wt.%, less than or equal to about 10 wt.%, less than or equal to about 9 wt.%, less than or equal to about 8 wt.%, less than or equal to about 7 wt.%, less than or equal to about 6 wt.%, less than or equal to about 5 wt.%, less than or equal to about 4 wt.%, less than or equal to about 3 wt.%, less than or equal to about 2 wt.%, or less than or equal to about 1 wt.%.
[0092] By including the soft particles within the above range, when the polishing slurry according to some example embodiments is applied to a chemical mechanical polishing process, the soft particles are in good contact with the nano abrasive particles, so that the polishing rate can be improved by effectively transferring the load applied from the polishing head to the nano abrasive particles.
[0093] In the polishing slurry according to some example embodiments, the soft particles and the nano-abrasive particles may be included in a weight ratio of about 0.1:1 to about 5:1. For example, the weight ratio of the soft particles and the nano-abrasive particles may be about 0.1:1 to about 4.5:1, about 0.2:1 to about 4.5:1, about 0.3:1 to about 4.5:1, about 0.5:1 to about 4.5:1, about 0.7:1 to about 4.5:1, about 0.7:1 to about 4:1, about 0.7:1 to about 3.8:1, about 0.7:1 to about 3.5:1, about 0.7:1 to about 3:1, about 1:1 to about 4.5:1, about 1:1 to about 4:1, about 1:1 to about 3.8:1, about 1:1 to about 3.5:1, about 1:1 to about 3:1, about 1:1 to about 3:1, about 1:1 to about 3:1, about 1:1 to about 3:1, about 1:1 to about 3:1, about 1:1 to about 3:1, about 1:1 to about 3:1. To about 4.5:1, about 1.4:1 to about 4.5:1, about 1.5:1 to about 4.5:1, about 1.5:1 to about 4:1, about 1.5:1 to about 3.5:1, about 1.5:1 to about 3:1, about 1.7:1 to about 4.5:1, about 2:1 to about 4.5:1, about 2:1 to about 4:1, about 2:1 to about 3.8:1, about 2:1 to about 3.5:1, about 2:1 to about 3:1, about 2.5:1 to about 4:1, about 2.5:1 to about 3.8:1, about 2:1 to about 3.5:1, about 2:1 to about 3:1, about 2.5:1 to about 4:1, about 2.5:1 to about 3.5:1, or about 2.5:1 to about 3:1, but is not limited thereto.
[0094] Alternatively, in the polishing slurry according to some example embodiments, the soft particles and the nano-abrasive particles may be included in a volume ratio of about 1: 1 to about 30: 1. For example, the volume ratio of the soft particles and the nano-abrasive particles may be about 1: 1 to about 25: 1, about 1: 1 to about 23: 1, about 1: 1 to about 20: 1, about 1: 1 to about 18: 1, about 1: 1 to about 17: 1, about 1: 1 to about 15: 1, about 1: 1 to about 13: 1, about 1: 1 to about 12: 1, about 1: 1 to about 10: 1, about 1: 1 to about 8: 1, about 1: 1 to about 7: 1, about 1: 1 to about 5: 1, about 1: 1 to about 4.5: 1, about 1: 1 to about 4: 1, about 1: 1 to about 3.5: 1, about 1: 1 to about 3: 1, about 1: 1 to about 2.5: 1, or about 1: 1 to about 2: 1, but is not limited thereto.
[0095] When the weight ratio and / or volume ratio of the soft particles and the nano-abrasive particles is within the above range, when a polishing slurry containing these particles is applied to a chemical mechanical polishing process, the soft particles are in good contact with the nano-abrasive particles, and the load applied from the polishing head is well transferred to the nano-abrasive particles, thereby improving the polishing rate.
[0096] Based on the total weight of the polishing slurry according to some example embodiments, the total amount of nano-abrasive particles and soft particles may be about 0.02 wt % to about 30 wt %. For example, based on the total amount of the polishing slurry, the total amount of nano-abrasive particles and soft particles may be greater than or equal to about 0.02 wt %, greater than or equal to about 0.03 wt %, greater than or equal to about 0.04 wt %, greater than or equal to about 0.05 wt %, greater than or equal to about 0.06 wt %, greater than or equal to about 0.07 wt %, greater than or equal to about 0.08 wt %, greater than or equal to about 0.09 wt %, greater than or equal to about 0.1 wt %, greater than or equal to about 0.15 wt %, greater than or equal to about 0.2 wt %, greater than or equal to about 0.4 wt %, greater than or equal to about 0.5 wt %, or greater than or equal to about 1 wt %. In addition, based on the total amount of polishing slurry, the total amount of nano abrasive particles and soft particles can be less than or equal to about 30 weight %, less than or equal to about 28 weight %, less than or equal to about 25 weight %, less than or equal to about 23 weight %, less than or equal to about 20 weight %, less than or equal to about 18 weight %, less than or equal to about 15 weight %, less than or equal to about 12 weight %, less than or equal to about 10 weight %, less than or equal to about 9 weight %, less than or equal to about 8 weight %, less than or equal to about 7 weight %, less than or equal to about 6 weight %, or less than or equal to about 5 weight %. Desired polishing rate and polishing efficiency can be obtained within the above range.
[0097] Polishing slurries according to some example embodiments can be prepared by simply mixing soft particles and nanoabrasive particles having the same zeta potential sign in a specific pH range. In some exemplary embodiments, polishing slurries according to some example embodiments can be prepared by mixing soft particles and nanoabrasive particles having the same zeta potential at a specific pH.
[0098] In addition to the soft particles and nano-abrasive particles, the polishing slurry according to some example embodiments may further include other components for forming the polishing slurry. For example, the polishing slurry may further include an additive, and the additive may be, for example, a chelating agent, an oxidizing agent, a surfactant, a dispersant, a pH adjuster, or any combination thereof, but is not limited thereto.
[0099] The chelating agent may be, for example, phosphoric acid, nitric acid, citric acid, malonic acid, a salt thereof, or any combination thereof, but is not limited thereto.
[0100] The oxidizing agent may be, for example, hydrogen peroxide, sodium hydroxide, potassium hydroxide, or any combination thereof, but is not limited thereto.
[0101] The surfactant may be an ionic or nonionic surfactant, and may be, for example, a copolymer of ethylene oxide, a copolymer of propylene oxide, an amine compound, or any combination thereof, but is not limited thereto.
[0102] Dispersant can promote the dispersion of soft particles and nano abrasive particles, and can include, for example, water-soluble monomers, water-soluble oligomers, water-soluble polymers, metal salts or any combination thereof. The weight-average molecular weight of the water-soluble polymer can be, for example, less than or equal to about 10,000 Daltons (Da), for example, less than or equal to about 5,000 Da, for example, less than or equal to about 3,000 Da and greater than or equal to about 1 Da, for example, greater than or equal to about 10 Da, greater than or equal to about 100 Da or greater than or equal to about 1,000 Da. Metal salts can be, for example, copper salts, nickel salts, cobalt salts, manganese salts, tantalum salts, ruthenium salts or any combination thereof. Dispersant can be, for example, poly (methyl) acrylic acid, (methyl) acrylic acid-maleic acid copolymer, acrylonitrile-butadiene-acrylic acid copolymer, carboxylic acid, sulfonic acid ester, sulfonic acid, phosphate ester, cellulose, glycol, its salt or any combination thereof, but is not limited thereto.
[0103] The pH adjuster may adjust the pH of the polishing slurry, and may include, for example, an acidic pH adjuster and an alkaline pH adjuster.
[0104] The acidic pH adjusting agent may include an inorganic acid, an organic acid, a salt thereof, or any combination thereof. The inorganic acid or its salt may include, for example, nitric acid, hydrochloric acid, phosphoric acid, sulfuric acid, hydrofluoric acid, bromic acid, iodic acid, or a salt thereof, and the organic acid or its salt may include, for example, formic acid, malonic acid, maleic acid, oxalic acid, adipic acid, citric acid, acetic acid, propionic acid, fumaric acid, lactic acid, salicylic acid, benzoic acid, succinic acid, phthalic acid, butyric acid, glutaric acid, glutamic acid, glycolic acid, lactic acid, aspartic acid, tartaric acid, or a salt thereof, but is not limited thereto.
[0105] Alkaline pH adjusters may include potassium hydroxide (KOH), sodium hydroxide (NaOH), ammonium hydroxide (NH 4 OH), tetramethylammonium hydroxide (TMAH), trimethylamine (TMA), or any combination thereof, but not limited thereto.
[0106] Each additive may be independently included in a small amount, for example, from about 1 ppm to about 100,000 ppm, but is not limited thereto.
[0107] The polishing slurry may further contain a solvent capable of dissolving or dispersing the above components, and the solvent may be, for example, water. The water may be, for example, distilled and / or deionized water.
[0108] When forming various structures, the aforementioned polishing slurry can be applied, for example, in a polishing process of a conductor such as a metal line or a shallow trench isolation (STI), or a polishing process of an insulator such as an insulating film. For example, the polishing slurry according to some example embodiments can be used to polish a conductor such as a metal line in a semiconductor substrate, and can be used to polish a conductor such as copper (Cu), tungsten (W), or an alloy thereof. In addition, as an example, the polishing slurry according to some example embodiments can be used during an STI manufacturing process.
[0109] In the following, reference Figures 2 to 8 , describing a process of manufacturing an STI by using a polishing slurry according to some example embodiments. Figures 2 to 8 It is a cross-sectional view showing each step of the STI manufacturing process.
[0110] First, if Figure 2 As shown in FIG. , silicon oxide (SiO 2 ) film 20, a silicon nitride (SiN) film 30, and a photoresist (photoresist) 40 are sequentially stacked on a silicon substrate 10. Since the semiconductor substrate, for example, the silicon substrate 10 and the silicon nitride (SiN) film 30 have poor adhesion, a silicon oxide (SiO 2 ) film 20. Silicon oxide (SiO 2 ) film 20 can be formed by oxidizing the surface of the silicon substrate 10. Since the silicon nitride (SiN) film 30 is thinner than the silicon oxide (SiO 2 ) film 20 is much harder, so when a chemical mechanical polishing (CMP) process is subsequently performed, the silicon nitride (SiN) film 30 can play a role in protecting the underlying layer from the CMP slurry. The silicon nitride (SiN) film 30 can be formed by a chemical vapor deposition (CVD) method. The photoresist 40 can be formed by coating a photosensitive resin composition for photoresist on the silicon nitride (SiN) film 30. The underlying film can be patterned by using the photoresist 40 through a photolithography process.
[0111] Then, if Figure 3 As shown, after a portion of the photoresist 40 film is removed by a photolithography process, the silicon nitride (SiN) film 30 and the silicon oxide (SiO 2 ) portion of the film 20 and even a portion of the silicon substrate 10 may be removed in the etching process to form the trench 10 a in the silicon substrate 10.
[0112] After forming the trench 10a, the remaining photoresist 40 is removed. Figure 4 As shown in FIG. Most of the photoresist 40 can be removed by wet etching using a chemical solution. Subsequently, by using oxygen (O 2) The remaining photoresist is removed by a plasma dry etching process.
[0113] Then, if Figure 5 As shown in FIG. 1 , the surface of the trench 10 a formed in the silicon substrate 10 is oxidized by thermal oxidation to form silicon oxide (SiO 2 ) film 20. The thermal oxidation process is used to restore the 2 ) The process of ion damage caused by plasma dry etching process.
[0114] Then, if Figure 6 As shown in FIG. 1 , the inside of the trench 10 a is filled with an oxide, wherein an oxide material having excellent gap filling characteristics and not generating voids, such as a TEOS (tetraethyl orthosilicate) precursor, can be used. TEOS is deposited inside the trench 10 a and on the entire surface of the device by using a high density plasma chemical vapor deposition (HDP CVD) method or the like to form silicon oxide (SiO 2 )50.
[0115] Subsequently, the chemical mechanical polishing (CMP) apparatus 400 described below is used to polish the substrate by using a polishing slurry according to some example embodiments. Figure 6 The surface of the laminate is such that Figure 7 As shown in , the upper surface of the stacked body can be planarized based on the surface of the silicon nitride (SiN) film 30. This process can be performed as follows: when the CMP process is applied, the CMP process is stopped at a point when the polishing rate is significantly reduced on the surface of the silicon nitride (SiN) film 30. As described above, the silicon nitride (SiN) film 30 is thinner than the silicon oxide (SiO 2 ) Film 20 is much harder.
[0116] After the planarization process, the Figure 7 The silicon nitride (SiN) film 30 shown in FIG. 1 remains in the upper portion of the stack, thereby completing the STI, wherein the silicon oxide (SiO 2 ) is formed inside the groove formed in the silicon substrate 10 and on the surface of the silicon substrate 10, such as Figure 8 as shown in .
[0117] In the following, reference Fig. 9 , a chemical mechanical polishing (CMP) apparatus 400 that can be used to fabricate STI will be described. Fig. 9 is a schematic diagram schematically showing an example chemical mechanical polishing apparatus according to some example embodiments.
[0118] The chemical mechanical polishing apparatus 400 may include, for example, a polishing head 401; a lower base 402; a platen 404 rotatably disposed on an upper surface of the lower base 402; a polishing pad 406 on the platen; a pad conditioner 408; and at least one polishing slurry supply device 409 configured to supply a polishing slurry 410 disposed near the polishing pad.
[0119] The pressing plate 404 may be rotatably disposed on the surface of the lower base 402. For example, the pressing plate 404 may receive rotational power from a motor disposed in the lower base 402. Therefore, the pressing plate 404 may rotate around an imaginary rotation axis perpendicular to the surface of the pressing plate 404. The imaginary rotation axis may be perpendicular to the surface of the lower base 402.
[0120] The platen 404 may include one or more supply lines through which a liquid (not shown) may be injected and discharged. For example, water may be injected and discharged into the platen 404 through the supply line to adjust the temperature of the platen 404. For example, cooling water may be injected and discharged into the platen 404 through the supply line, and thus, the temperature of the overheated platen 404 may be reduced. For example, hot water at a high temperature may be injected and discharged into the platen 404 through the supply line, causing the temperature of the platen 404 to increase.
[0121] The polishing pad 406 may be disposed on the surface of the platen 404 to be supported by the platen 404. The polishing pad 406 may rotate together with the platen 404. The surface of the polishing pad 406 may be rough. The polishing surface may contact the polishing object such as the semiconductor wafer 100 or the above-mentioned stacked body for forming STI (e.g., as shown in FIG. 1 ). Figures 2 to 8 The polishing pad 406 is directly in contact with a surface of the laminate (as shown in any one of the laminates) and the surface can be mechanically polished. The polishing pad 406 can be a porous material having a plurality of micro spaces, wherein the plurality of micro spaces can accommodate a polishing slurry located within the interior of the polishing pad 406 and / or within the micro cavities of the polishing pad 406, and the micro cavities are exposed to the polishing surface of the polishing pad 406.
[0122] The pad conditioner 408 may be disposed adjacent to the polishing pad 406 , and may adjust the condition of the polishing surface so that the surface of the object to be polished is effectively polished when performing a polishing process.
[0123] The polishing slurry supply device 409 may be disposed adjacent to the polishing pad 406, and may supply the polishing slurry to the polishing pad 406. The polishing slurry supply device 409 may include a nozzle capable of supplying the polishing slurry onto the polishing pad 406 during the polishing process, and a voltage supply unit (not shown) capable of applying a predetermined voltage to the nozzle. The polishing slurry in the nozzle may be loaded by the voltage applied from the voltage supply unit and discharged toward the polishing pad 406.
[0124] Chemical mechanical polishing may include, for example, arranging the surface of an object to be polished, such as a semiconductor wafer 100, and a polishing pad 406 to face each other, supplying polishing slurry from a polishing slurry supply device 409 between the surface of the semiconductor wafer 100 and the polishing pad 406; and applying pressure through a polishing head 401 to bring the surface of the semiconductor wafer 100 into contact with the polishing pad 406 for polishing.
[0125] In one example, in the supply of the polishing slurry, the polishing slurry can be supplied at a rate of, for example, about 10 ml / min to about 300 ml / min, for example, about 10 ml / min to about 250 ml / min, about 10 ml / min to about 200 ml / min, about 50 ml / min to about 250 ml / min, about 50 ml / min to about 200 ml / min, about 80 ml / min to about 250 ml / min, about 100 ml / min to about 200 ml / min, about 110 ml / min to about 180 ml / min, or about 120 ml / min to about 150 ml / min, but is not limited thereto.
[0126] In the step of performing polishing, for example, the semiconductor wafer 100 (which may include, for example, Figure 6 ) is in contact with the polishing pad 406, and polishing can be performed by mechanical friction by rotating the polishing pad 406 relative to the surface of the semiconductor wafer 100. For example, in the step of performing polishing (e.g., accompanied by polishing of the surface of the semiconductor wafer 100 close to and / or facing the polishing pad 406), a pressure of about 1 psi to about 10 psi, for example, about 1 psi to about 8 psi, about 2 psi to about 7 psi, about 2 psi to about 6 psi, about 2 psi to about 5 psi, or about 3 psi to about 4 psi may be applied between the polishing pad 406 and the object to be polished by the polishing head 401, so that the pressure is applied to the surface of the object to be polished. For example, pressure may be applied between the polishing pad 406 and the semiconductor wafer 100, so that pressure is applied to the surface of the semiconductor wafer 100 close to and / or facing the polishing pad 406. For example, the semiconductor wafer 100 may include a metal wire close to the surface of the semiconductor wafer 100 close to and / or facing the polishing pad 406, and the polishing of the surface of the semiconductor wafer 100 may polish the metal wire.
[0127] Although the STI manufacturing method according to the example has been described above, it is not limited thereto and can be applied to semiconductor devices of various structures. The method of manufacturing such a semiconductor device includes arranging the surface of a semiconductor substrate and the surface of a polishing pad close to each other, supplying a polishing slurry according to some example embodiments between the semiconductor substrate and the polishing pad, and polishing the surface of the semiconductor substrate by bringing the surface of the semiconductor substrate into contact with the surface of the polishing pad.
[0128] The description herein with respect to the semiconductor wafer 100 may be applied equally and interchangeably to semiconductor substrates, laminates, and the like.
[0129] As described herein, a "semiconductor substrate" may include one or more structures of a semiconductor device, including, for example, one or more of the following: a semiconductor substrate, an interlayer insulating film, a barrier layer and / or a metal layer, or a stacked body, wherein the stacked body may include silicon oxide (SiO 2 ) film 20, silicon nitride (SiN) film 30, photoresist 40, and / or silicon oxide (SiO 2 ) one or more of layer 50.
[0130] As described herein, the surface of a "semiconductor substrate" may include one or more surfaces of one or more structures of a semiconductor device, including, for example, a semiconductor substrate, or one or more surfaces of an insulating layer, a barrier layer and / or a metal layer in an intermediate layer, or a silicon oxide (SiO 2 ) film 20, silicon nitride (SiN) film 30, photoresist 40, and / or silicon oxide (SiO 2 ) one or more surfaces of layer 50.
[0131] As described herein, steps of polishing, polishing the surface of a "semiconductor substrate", etc. may be understood to include polishing (e.g., as part of planarization) one or more surfaces of a semiconductor device, such as an interlayer insulating film, a barrier layer, and / or a metal film.
[0132] In some example embodiments, one or more semiconductor devices (e.g., a semiconductor wafer, one or more semiconductor chips singulated from the semiconductor wafer, etc.) may be manufactured based on performing the polishing. Such one or more semiconductor devices may be incorporated into (e.g., applied to) electronic devices, including, for example, Fig.21 As a result, an electronic device configured to have improved performance and integration (e.g., improved compactness) can be manufactured based on: being manufactured to include one or more high-performance, highly integrated semiconductor devices (e.g., having a structure having a fine pitch of about 10 nm or less) based on a structure surface polished using the polishing slurry 410 according to any example embodiment.
[0133] Fig.21 is a schematic block diagram of an electronic device 300 according to some example embodiments.
[0134] refer to Fig.21, the electronic device 300 may include a processor 310, an input / output device (I / O) 320, a storage device 330, and a wireless interface 340, which are respectively connected to each other via a bus 350. In some example embodiments, one or more of the input / output device 320 or the wireless interface 340 may be omitted from the electronic device 300. At least one of the processor 310, the input / output device 320, the storage device 330, or the wireless interface 340 may include one or more semiconductor devices manufactured according to any example embodiment (e.g., using the polishing slurry 410 according to any example embodiment). In some example embodiments, the electronic device 300 may be configured to control a variety of devices for manufacturing semiconductor devices (including, for example, controlling some or all of the chemical mechanical polishing device 400) and / or a variety of devices for manufacturing electronic devices so that the various devices manufacture semiconductor devices, electronic devices including the same, and the like.
[0135] The processor 310 may include at least one of the following: a microprocessor, a digital signal processor, or a processing device similar thereto. The input / output device 320 may include at least one of the following: a keypad, a keyboard, or a display. The storage device 330 may include a non-transitory computer-readable medium (e.g., a solid-state drive storage device) configured to store a program of instructions. The storage device 330 may be used to store commands executed by the processor 310. For example, the storage device 330 may be used to store user data. The electronic device 300 may use the wireless interface 340 to transmit / receive data through a wireless communication network. The wireless interface 340 may include an antenna and / or a wireless transceiver.
[0136] The electronic device 300 and / or any portion thereof (e.g., the processor 310, the storage device 330, the input / output device 320, the wireless interface 340, any portion thereof, etc.) may include, may be included in, and / or may be implemented by: one or more instances of a processing circuit system, such as hardware including logic circuits; a hardware / software combination, such as a processor executing software; or any combination thereof. For example, the processing circuit system may more specifically include, but is not limited to, a central processing unit (CPU), an arithmetic logic unit (ALU), a graphics processing unit (GPU), an application processor (AP), a digital signal processor (DSP), a microcomputer, a field programmable gate array (FPGA), and a programmable logic unit, a microprocessor, an application specific integrated circuit (ASIC), a neural network processing unit (NPU), an electronic control unit (ECU), an image signal processor (ISP), etc. In some example embodiments, the processing circuit system may include a non-transitory computer-readable storage device (e.g., memory) storing a program of instructions, such as a solid-state drive (SSD) device, and a processor (e.g., CPU) configured to execute the program of instructions to implement (realize) some or all of the functions and / or methods performed by the electronic device 300 and / or any device and / or method implemented and / or controlled thereby (e.g., to perform Figures 2 to 8 Some or all of the methods shown in , for example, based on control Fig. 9 The chemical mechanical polishing equipment shown in ).
[0137] Hereinafter, the embodiments are described in more detail with reference to examples. However, these examples are exemplary, and the scope of claims is not limited thereto.
[0138] Example
[0139] Reference Example 1: Measurement of polishing rate of slurry including nanoabrasive particles or soft particles alone
[0140] Polystyrene particles having an average particle size of about 92 nm, a Mohs hardness of about 1.5 to 2.5, and a substantially spherical shape were prepared as soft particles. As nanoabrasive particles, two types of cerium oxide (CeO 2 ) having different average particle diameters (D50=15 nm or 25 nm) manufactured by Ditto Technology were prepared. 2 )(Mohs hardness: 7.5 to 8).
[0141] All slurries included water as a solvent, and the soft particles and nano abrasive particles were used in an amount of 0.2% based on the total weight of each slurry, and pH was adjusted to 4 by adding nitric acid and ammonia water thereto. In addition, CTAB (cetyltrimethylammonium bromide) was added as an additive at 0.5% by mass of cerium oxide.
[0142] The semiconductor wafer was polished using each slurry prepared as described above according to the following polishing rate evaluation method, and the results are shown in Fig.10 middle.
[0143] like Fig.10 As shown in , for two types of slurries (STD (15 nm) and STD (25 nm)) with different particle sizes of ceria used alone, one slurry (STD (25 nm)) using ceria with a larger particle size exhibited a much higher polishing rate than another slurry (STD (15 nm)) using ceria with a smaller particle size, but the slurry including the soft particles alone exhibited almost no polishing. In other words, the soft particles used alone exhibited substantially no polishing performance due to their low Mohs hardness.
[0144] Evaluation of polishing rate (MRR, material removal rate)
[0145] A silicon wafer of 40 mm×40 mm size covered with a silicon oxide film was used as a polishing wafer, and the polishing rate of the silicon oxide film was evaluated using each polishing slurry using the following polishing conditions.
[0146] The thickness of the silicon oxide film before and after polishing was measured, and the thickness of the silicon oxide film per unit polishing time (1 minute) was calculated. For thickness measurement, the central portion of the silicon oxide film was measured 5 times using a reflectometer (ST5030-SL, K-MAC), and the average value was used.
[0147] Polishing conditions are as follows:
[0148] (1) CMP equipment: POLI-400 (GnP Tech. Co.)
[0149] (2) Polishing pad: IT-2000 (KPX Chemical Co.)
[0150] (3) Polishing head rotation speed: 130rpm
[0151] (4) Polishing plate rotation speed: 130rpm
[0152] (5) Applied pressure: 5.5 psi
[0153] (6) Polishing slurry supply rate: 150 ml / min.
[0154] Examples 1 to 3: Measurement of polishing rates of slurries comprising both nanoabrasive particles and soft particles
[0155] Slurry A was prepared by mixing cerium oxide (0.2 wt%) having a size of 25 nm used in Reference Example 1 with polystyrene particles (0.25 wt%) having an average size of 92 nm and having a positive zeta potential at pH 4, and slurry B was prepared by mixing the same cerium oxide (0.2 wt%) as above with polystyrene particles (0.25 wt%) having a different average particle size of 107 nm and having the same positive zeta potential at pH 4. Then, the polishing rates of slurry A and slurry B were respectively measured by using the polishing rate evaluation method as described above, and the results were compared with those of reference example 1. Fig.10 The corresponding results of the reference example 1 slurry STD (25nm) are shown together with the description and Fig.11 In each example of the present application, the Mohs hardness of the polystyrene particles is the same as that in Reference Example 1, and in addition to the nanoabrasive particles, the polystyrene particles, and water, the polishing slurry further includes CTAB in an amount of 0.5% by mass of the nanoabrasive particles, unless otherwise specified.
[0156] In addition, slurry A was prepared by mixing cerium oxide (0.2 wt%) having a size of 15 nm used in Reference Example 1 with polystyrene particles (0.5 wt%) having an average size of 130 nm and having a positive zeta potential at pH 4, and slurry B was prepared by mixing the same cerium oxide (0.2 wt%) as above with polystyrene particles (0.5 wt%) having a different average particle size of 157 nm and having the same positive zeta potential at pH 4. Then, the polishing rates of slurry A and slurry B were respectively measured by using the polishing rate evaluation method as described above, and the results were compared with those of reference example 1. Fig.10 The corresponding results of the reference example 1 slurry STD (15nm) are shown together with the description and Fig.12 (Example 2).
[0157] In addition, similar to Reference Example 1, a slurry including 8 wt % of silica having a particle size of 7 nm alone was prepared, and slurry A was prepared by mixing 8 wt % of the same silica as above and 3.6 wt % of polystyrene particles having a negative zeta potential at pH 4. Then, the polishing rates of the slurry including silica alone and slurry A were measured by using the same method as above, and the results are shown in FIG. Fig.13 (Example 3).
[0158] like Figures 11 to 13As shown in , a slurry including nanoabrasive particles together with soft particles (polystyrene particles) having the same sign of zeta potential as that of each of the nanoabrasive particles (wherein the soft particles alone do not exhibit polishing performance) exhibits a significantly improved polishing rate compared to the case where nanoabrasive particles (cerium dioxide or silicon dioxide) are included alone.
[0159] Example 4: Measurement of polishing effect according to the amount of soft particles
[0160] A slurry (STD: standard) including 0.2 wt% of the cerium oxide particles having a size of 25 nm used in Reference Example 1 and having a pH adjusted to 4 was prepared (i.e., STD (25 nm) as described herein). In addition, a slurry including the same cerium oxide particles as above and polystyrene particles having an average particle size of 83 nm and a positive zeta potential at pH 4 in respective amounts of 0.026 wt%, 0.132 wt%, 0.25 wt%, 0.5 wt%, and 1.0 wt% was prepared. Then, the polishing rate of the slurry was measured by using the method described above, and the results are shown in FIG. Fig.14 middle.
[0161] like Fig.14 As shown in , the more polystyrene particles are added within a predetermined content range, the higher the polishing rate is obtained, but if the polystyrene particles are added exceeding the predetermined content, the polishing rate is reduced.
[0162] Example 5: Comparison of the effects depending on whether the signs of the zeta potentials of soft particles and nano-abrasive particles are the same
[0163] A slurry including 0.026 wt % of polystyrene particles having a positive zeta potential at pH 4 and an average particle size of 86 nm and 0.2 wt % of cerium dioxide having a particle size of 25 nm (positive A) and a slurry identical to positive A but only changing the average particle size of the polystyrene particles to 128 nm (positive B) were prepared.
[0164] In addition, a slurry including 0.026 wt % of polystyrene particles whose surface was modified to have a negative zeta potential instead of a positive zeta potential at pH 4 and having an average particle size of 83 nm and 0.2 wt % of cerium dioxide having a particle size of 25 nm (negative A), and a slurry (negative B) which was the same as negative A but only the average particle size of the polystyrene particles was changed to 92 nm were prepared.
[0165] The polishing rates of positive A, positive B, negative A and negative B slurries and a slurry alone including 0.2 wt % of cerium oxide particles having a size of 25 nm without soft particles such as polystyrene particles were evaluated by using the method described above, and the results are shown in Fig.15 middle.
[0166] like Fig.15 As shown in , positive A and positive B slurries (in which ceria exhibiting a positive zeta potential at pH 4 and polystyrene soft particles having the same zeta potential sign as that of ceria are combined) exhibit polishing rates increased to about 6 times and about 9 times, respectively, compared to a slurry including ceria alone. However, negative A and negative B slurries in which polystyrene soft particles having a zeta potential sign opposite to that of ceria are included exhibit polishing rates similar to that of a slurry including ceria alone (in the case of negative B), or lower than that of a slurry including ceria alone (in the case of negative A).
[0167] Therefore, the case of further including soft particles having the same sign of zeta potential as that of the nano abrasive particles according to some example embodiments exhibits a significantly improved polishing rate compared to the case of solely including abrasive particles having a very small particle size.
[0168] In addition, a photograph of the negative A paste is shown in Fig.16 In. Reference Fig.16 , the negative A slurry to which soft particles exhibiting a zeta potential sign opposite to that of ceria were added appeared turbid because the nanoabrasive particles (ceria) and the soft particles (polystyrene particles) were adsorbed to each other to form a precipitate.
[0169] The above trend was also confirmed in the slurry using silica particles.
[0170] Silica particles exhibit a negative zeta potential at a pH of about 2.5 or higher. If soft particles exhibiting a positive zeta potential in the same pH range are added to these silica particles, a precipitate is formed due to adsorption of the two types of particles.
[0171] In particular, if Fig.17 As shown in , if 3.58 wt % of polystyrene particles exhibiting a positive zeta potential at the same pH and having an average size of 88 nm are added to a bottle containing an aqueous solution including 8.8 wt % of silica having a particle size of 7 nm, after the corresponding solution is poured out, a precipitate adheres to the wall of the bottle, making the wall of the bottle look turbid ( Fig.17 However, if 3.58 wt% of polystyrene particles having an average size of 88 nm and exhibiting a negative zeta potential at the same pH are added to an aqueous solution comprising 8.8 wt% of silica particles having a particle size of 7 nm, the wall of the bottle remains transparent ( Fig.17 on the right of the photo).
[0172] In addition, the polishing rates of a (negative) slurry prepared by adding 3.58 wt% of polystyrene particles having an average size of 88 nm and a negative zeta potential to silica (8.8 wt% and a size of 7 nm), and a (positive) slurry prepared by adding 3.58 wt% of polystyrene particles having an average size of 88 nm and a positive zeta potential to silica (8.8 wt% and a size of 7 nm) were evaluated, and the results are shown in Fig.18 In. Fig.18 In, similar to Fig.15 , the negative slurry to which polystyrene particles having the same zeta potential sign as that of silica particles were added exhibited an increased polishing rate of almost 4 times. However, the positive slurry to which soft particles having a zeta potential sign opposite to that of silica were added exhibited a decreased polishing rate of about 1 / 3 of the polishing rate of the slurry including silica alone.
[0173] Example 6: Comparison of the effect of reducing surface scratches due to the addition of soft particles
[0174] The presence or absence of scratches on the surface of the polished object in the case of adding soft polystyrene particles to cerium dioxide or silicon dioxide was examined by surface analysis of the surface of the polished wafer by AFM (atomic force microscopy) compared with the case of including cerium dioxide having a particle size of 25 nm and 50 nm alone or including silicon dioxide having a particle size of 7 nm alone, and the results are shown in Fig.19 and 20 middle.
[0175] like Fig.19 As shown in Fig.19 The left photo, where the amount of cerium dioxide is 0.2 wt%) is reduced to 25 nm (see Fig.19 In the middle photo of FIG. 1 , where the amount of cerium dioxide is 0.2 wt %), the surface scratches are reduced. On the other hand, even if cerium dioxide (0.2 wt %) having a size of 25 nm is mixed with polystyrene particles having an average size of 83 nm (see FIG. 1 ). Fig.19 The right side of the photograph, in which the amount of polystyrene particles is 0.026 wt%), also produces scratches at a level similar to the case of using cerium dioxide (0.2 wt%) with a size of 25 nm alone. In other words, even if soft particles with a large size are added, surface scratches are not increased due to the soft particles.
[0176] In addition, refer to Fig. 20 , a slurry comprising silicon dioxide having a size of 7 nm alone (reference Fig. 20, wherein the amount of silicon dioxide is 8.8 wt %) and a slurry comprising 3.58 wt % of polystyrene particles having an average size of 100 nm together with the silicon dioxide (reference Fig. 20 The right photograph of , in which the amount of silica is 0.2 wt %) shows the generation of surface scratches at a similar level. In other words, even if soft particles with a large particle size are added, the generation of surface scratches is not increased by the soft particles.
[0177] As described above, the polishing slurry according to some embodiments, which includes nano-abrasive particles and soft particles having substantially no polishing performance due to a lower Mohs hardness than the nano-abrasive particles and having the same zeta potential sign as that of the nano-abrasive particles in a specific pH range, exhibits an excellent effect of significantly improving the polishing rate, despite the use of abrasive particles having a very small particle size. Therefore, the polishing slurry according to some embodiments can be used to quickly polish a structure having a fine pitch structure without surface damage.
[0178] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it will be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. Polishing slurry, including: Nano-abrasive particles having a Mohs hardness greater than 5, and soft particles having a lower Mohs hardness than the nano abrasive particles, The nano-abrasive particles and the soft particles in the slurry have the same zeta potential sign as each other.
2. The polishing slurry according to claim 1, wherein the soft particles comprise polymer particles. 3 . The polishing slurry according to claim 1 , wherein a difference in Mohs hardness between the soft particles and the nano abrasive particles is greater than or equal to 1. 4 . The polishing slurry according to claim 1 , wherein the soft particles have an average particle size larger than that of the nanoabrasive particles.
5. The polishing slurry according to claim 1, wherein The average particle size of the nano-abrasive particles is less than or equal to 100 nanometers, and / or The average particle size of the soft particles is 50 nm to 20 μm. 6 . The polishing slurry according to claim 1 , wherein the nanoabrasive particles and the soft particles have the same zeta potential as each other in the slurry.
7. The polishing slurry of claim 1, wherein the soft particles comprise polystyrene, styrene-based copolymers, poly(alkyl (meth)acrylates), acrylic copolymers, polyvinyl chloride, polyacetal, saturated polyester, polyamide, polyimide, poly(amide-imide) copolymer, polycarbonate, phenoxy resin, polyolefin, olefin-based copolymer, polyurea, polyurethane, melamine resin, epoxy resin, or any combination thereof.
8. The polishing slurry according to claim 1, wherein the nanoabrasive particles comprise metal oxides, metal nitrides, metal fluorides, metal carbides, or any combination thereof.
9. The polishing slurry according to claim 8, wherein The metal oxide includes silicon oxide, cerium oxide, titanium oxide, zirconium oxide, aluminum oxide, molybdenum oxide, ruthenium oxide, tantalum oxide, tungsten oxide, or any combination thereof. The metal nitride includes silicon nitride, aluminum nitride, titanium nitride, boron nitride, or any combination thereof, The metal fluoride comprises calcium fluoride CaF2, selenium fluoride SeF4, tellurium fluoride TeF4, or any combination thereof, and The metal carbide includes tantalum carbide, boron carbide, or any combination thereof.
10. The polishing slurry according to claim 1, wherein the soft particles are included in the polishing slurry in an amount of 0.01 wt% to 15 wt%, and the nano abrasive particles are included in the polishing slurry in an amount of 0.01 wt% to 15 wt%, based on the total weight of the polishing slurry.
11. The polishing slurry according to claim 1, wherein The soft particles and the nano abrasive particles are included in the polishing slurry in a weight ratio of 0.1:1 to 5:1, or The soft particles and the nano abrasive particles are included in the polishing slurry in a volume ratio of 1:1 to 30:
1.
12. The polishing slurry according to claim 1, wherein the soft particles and / or the nano-abrasive particles are spherical.
13. The polishing slurry according to claim 1, wherein in the slurry, both the soft particles and the nano-abrasive particles have a positive zeta potential, or both the soft particles and the nano-abrasive particles have a negative zeta potential.
14. The polishing slurry according to claim 1, wherein the polishing slurry further comprises a chelating agent, an oxidizing agent, a surfactant, a dispersant, a pH adjuster, or any combination thereof.
15. A method for manufacturing a semiconductor device, comprising: placing a surface of the semiconductor substrate and a surface of the polishing pad close to each other, supplying the polishing slurry according to any one of claims 1 to 14 between the semiconductor substrate and the polishing pad, and The surface of the semiconductor substrate is polished by bringing the surface of the semiconductor substrate into contact with the surface of the polishing pad. 16 . The method according to claim 15 , wherein supplying the polishing slurry between the semiconductor substrate and the polishing pad is performed at a rate of 10 ml / min to 300 ml / min. 17 . The method of claim 15 , wherein the polishing of the surface of the semiconductor substrate is performed at a pressure of 1 psi to 10 psi against the surface.
18. The method of claim 15, wherein the semiconductor substrate includes metal lines proximate to a surface of the semiconductor substrate, and the polishing of the surface of the semiconductor substrate polishes the metal lines.
Citation Information
Patent Citations
Aqueous formulation comprising 1-(4-{[4-(dimethylamino)piperidin-1-yl]carbonyl}phenyl)-3-[4-(4,6-dimorpholin-4-yl-1,3,5-triazin-2-yl)phenyl]urea
KR1020230142810A
Measuring devices and measuring systems
KR1020240144114A